Conservative treatment of bronchobiliary fistula evaluated with magnetic resonance imaging - Adžić-Vukičević, Tatjana; Blanka, Ana Z.; Ilić, Aleksandra M.; Raljević, Snežana V.; Maksimović, Ružica M.; Djuranović, Srdjan P. (Vojnosanitetski pregled, 2015)
Introduction. Bronchobiliary fistula (BBF) is a pathological communication between the bronchial system and the biliary tree that presents with bilioptysis. Many conditions can cause its development. There is still no optimal therapy for BBF. Conservative treatment is rarely indicated, as was published before in a few cases. Case report. We presented a 71-year-old Caucasian Serbin woman with BBF secondary to previous laparotomy due to multiple echinococcus liver cysts. The diagnosis was established by the presence of bilirubin and bile acids in sputum and magnetic resonance cholangiopancreatography (MRCP). A repeat MRCP performed after conservative procedure, did not reveal fistulous communication. Conclusion. We suggest that in small and less severe fistulas between the biliary and the bronchial tract, conservative treatment may be used successfully, and invasive treatment methods are not needed in all patients.
Keywords: bronchial fistula; biliary fistula; diagnosis; magnetic resonance imaging; drug therapy